Determining Nutritional Status of the Rice Farmers Participating in IFAD-VCD Programme in Niger State of Nigeria - Sadiq, MS; Singh, IP; Ahmad, MM; Usman, BI; Yunusa, J.B; Ahmad, U (Journal of Agricultural Extension Management, 2020)
Most of the research on the impact of agricultural programmes on food security of farming households in Nigeria has been centered on the expenditure without having a critical investigation of the diet composition of the farmers. It is in this context that this research was conceptualized to study the nutritional status of the rice farmers participating in IFAD-VCD programme in Niger State of Nigeria. A representative sample size of 111 active participating farmers was selected and data was collected from the chosen farmers through a structured questionnaire, complemented with an interview schedule. The collected data were analyzed using both descriptive and inferential statistics. The results showed that the programme had an impact on the nutritional status of the participants, as their calorie intake per-head/day, after participating in the programme exceeded the recommended benchmark of 2250kcal/head/day for sub-Saharan Africa by 60.82 per cent. However, the recommended calorie consumption of the farmers was observed to be affected due to large household size, high dependency ratio, fear of default and delinquency owing to credit, non-effective extension service delivery owing to poor motivation of change agent and fear of managerial inefficiency in resource allocation owing to farming experience. Therefore, the study recommends that both public and private organizations with an agricultural mandate should make provision of consumption credit so as to enhance availability, utilization and stability of farm family food security in the studied area